Cord C-reactive protein as a marker for early onset neonatal sepsis children - Patrick, Reeba; Rajan, Aswathy; Shriyan, Ashvij (International Journal of Contemporary Pediatrics, 2017)
Background: Of the 2.8 million neonatal deaths, worldwide, 0.43 million is contributed by sepsis alone. The objective of this study was to determine the levels of umbilical cord C-reactive protein and assess the suitability of this test in diagnosing early onset sepsis in newborns born to mothers with no risk factors for intrapartum infection. To determine the influence of other factors such as parity, birth weight and mode of delivery on the levels of cord CRP. Methods: CRP levels in cord blood were estimated for 103 consecutive newborns delivered at a tertiary care teaching hospital. These babies were monitored for signs of sepsis for 72 hours and were later followed up with serum CRP and blood cultures. Results: A prospective cohort study of 103 consecutive newborns were taken of which 53.4% were male babies. Comparison of cord CRP levels of baseline characteristics revealed significant elevation in babies born to multipara mothers (p = 0.0028) and in low birth weight babies (p = 0.05), while there were no significant changes in different modes of delivery. The mean cord CRP of the study group was 0.694±0.2979. Out of 104 babies, 16 had elevated cord CRP (above 1.1mg/l) of these, 12 babies were later confirmed to have sepsis. The mean cord CRP level in babies with EOS was 1.3±0.255 (p = 0.001). A sensitivity of 100%, specificity of 90.9%, positive predictive value of 75% and negative predictive value of 100% was determined. Conclusions: This study confirms that cord CRP is an effective marker to predict EONS. An optimal concentration of cord CRP > 1.1 mg/L has maximal sensitivity and specificity to predict EONS.